Red blood cell alloimmunization in sickle cell disease and in thalassaemia: current status, future perspectives and potential role of molecular typing. (9th October 2013) - Matteocci, A.; Pierelli, L.
<x xml:space="preserve">Abstract</x> Red blood cell (RBC) transfusions are a milestone in the treatment for sickle cell anaemia (SSA) and for thalassaemia. RBC alloimmunization remains a major challenge of chronic transfusion therapy, and it can lead to adverse life‐threatening events. The alloimmunization risk could depend on multiple factors such as the number of transfusions and, most of all, the genetic background. Different ethnic groups are predisposed to immunization because of a significant degree of RBC antigenic mismatch between donor and recipient. There is no universal agreement and standards for the most appropriate selection of RBC units in chronically transfused subjects. Current practice only deals with compatibility of ABO, Rh and K antigens. Molecular RBC antigenic matching extended to other blood group systems is an innovative strategy to ensure a better quality and effectiveness of transfusion therapy.